Kecerdasan Dan Kepribadian Siswa di SMP IT Fathona Palembang Dan Pengaruhnya Terhadap Kemampuan Berbicara - Nurul Hidayah; Mukmin Mukmin; Monika Rahma (Taqdir, 2021)
Speech ability was influenced by several factors including intelligence and personality. SMP IT fathonah has used stifin test in knowing the intelligence and personality of students, the test results are then not only optimized in learning but also in 3 Lingual programs and Arabic-speaking environments. This study uses mixed method method. With qualitative and quantitative approach. The samples in this study were purposive samples with a total of 28 students. The data analysis technique in this study uses the Two Way Anova test formula with SPSS. The results of this study showed that intelligence affects students' speech ability with a degree of significance of 0.003. While personality does not affect students' speech ability because it has a significance of 0.548. But the two variables together affected students' speaking skills by 65.4%. From the data it can be stated that the personality of a student can not be expressed significantly because personality can be affected by other factors for example by motivation, or other psychological elements, while intelligence can affect speech skills significantly because intelligence can certainly support the growth of skills learned by students.